2014
DOI: 10.1007/s13361-014-0873-4
|View full text |Cite
|
Sign up to set email alerts
|

More Than Charged Base Loss — Revisiting the Fragmentation of Highly Charged Oligonucleotides

Abstract: Tandem mass spectrometry is a well-established analytical tool for rapid and reliable characterization of oligonucleotides (ONs) and their gas-phase dissociation channels. The fragmentation mechanisms of native and modified nucleic acids upon different mass spectrometric activation techniques have been studied extensively, resulting in a comprehensive catalogue of backbone fragments. In this study, the fragmentation behavior of highly charged oligodeoxynucleotides (ODNs) comprising up to 15 nucleobases was inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 42 publications
4
16
0
Order By: Relevance
“…Moreover, the isotopic distributions between the theoretical and experimental isotopic clusters from cyanate-lost precursors were shown to be inconsistent. 39 Our data sets expanded on previous results and provided accurate isotopic cluster matches. We compared the occurrence frequency of these two types of partial base losses between different oligo sequences under several charge states.…”
Section: Cyanate Anion Losses From Rna Oligos With 3′-u Were Dominant...mentioning
confidence: 56%
See 2 more Smart Citations
“…Moreover, the isotopic distributions between the theoretical and experimental isotopic clusters from cyanate-lost precursors were shown to be inconsistent. 39 Our data sets expanded on previous results and provided accurate isotopic cluster matches. We compared the occurrence frequency of these two types of partial base losses between different oligo sequences under several charge states.…”
Section: Cyanate Anion Losses From Rna Oligos With 3′-u Were Dominant...mentioning
confidence: 56%
“…The phenomenon of precursor charge-state-dependent base losses revealed that highly-charged RNA oligos increased the Coulomb repulsion between a charged nucleobase and the sugar, thus improving the chance of nucleobase release via glycosidic bond cleavage. 39 We then integrated seq-ion and nucleobase loss behavior data to determine how these trends changed quantitatively with the charge state. The data showed that the fractional abundance of seq-ions in the CID spectra decreased from 73% to 45%, whereas the neutral and charged nucleobase-loss precursor ions increased from 22% to 55%, when the charge state increased from -1 to -5 (Figure 6d).…”
Section: Nucleobase Losses From Precursors Were Markedly Increased At...mentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of modified RNAs by tandem mass spectrometry has become routine thanks to numerous fundamental studies by several research groups. [62][63][64] Sequence-specific information can be generated by applying energy to intact RNA oligomers in the gas phase, leading to predictable backbone fragmentation, which can locate modifications. More specifically, when activated using collision induced dissociation (CID), oligoribonucleotides typically fragment along the phosphodiester backbone to generate two separate mass ladders.…”
Section: Tandem Mass Spectrometrymentioning
confidence: 99%
“…Although CID of oligonucleotides predominately generates a-B and w type fragment ions (nomenclature of McLuckey et al [3]), generation of unidentifiable product ions and alternative fragmentation pathways (in CID and other fragmentation techniques) have also been reported [12][13][14][15]. For example, Juhasz et al reported generation of six unusual/unidentifiable high intensity product ion peaks from the DNA oligonucleotide, CAC ACG CCA GT [12]; these authors purported that the presence of unidentifiable fragment ions may make MS based de novo sequencing of some oligonucleotides impractical [12].…”
Section: Introductionmentioning
confidence: 99%